Pengaruh Brand Image Dan Kepercayaan Pelanggan Terhadap Loyalitas pelanggan Kitaro Pada Agen Kitaro Toko Arra Kecamatan Pino Raya Kabupaten Bengkulu Selatan - Febrian Iskandar; Ade Tiara Yulinda (UNIVED Press, 2023)
Customer loyalty is the loyalty of consumers to a product/service. Several factors that influence customer loyalty are brand image and customer trust. This study aims to determine the effect of brand image and customer trust on customer loyalty for drinking water in the KitaRO brand packaging at the Kitaro agent, Arra Store, Pino Raya District, South Bengkulu Regency. This type of research is quantitative research with a descriptive approach. The population of this research is all customers of KitaRO branded bottled water at the KitaRO agent Toko Arra, Pino Raya District, South Bengkulu Regency. The number of research samples was 110 people. Data collection was done by observation and questionnaires. The data analysis technique used multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 2.188 + 1.082 X1 + 0.508 X2. The results of the analysis show that partially brand image has a positive and significant effect on customer loyalty (tcount = 10,929 and tsig = 0.000) and customer trust has a positive and significant effect on customer loyalty (tcount = 5.119 and tsig = 0.000). Simultaneously there is an effect of brand image and customer trust on customer loyalty (Fcount = 313.880 and Fsig = 0.000).It is recommended to the KitaRO Toko Arra agent to be able to increase customer loyalty by creating a high brand image and customer trust in drinking water products in the KitaRO brand packaging.